2021
DOI: 10.2337/dbi21-0029
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Induced New-Onset Diabetes: Trends and Technologies

Abstract: The coronavirus disease 2019 global pandemic continues to spread worldwide with approximately 216 million confirmed cases and 4.49 million deaths to date. Intensive efforts are ongoing to combat this disease by suppressing viral transmission, understanding its pathogenesis, developing vaccination strategies, and identifying effective therapeutic targets. Individuals with preexisting diabetes also show higher incidence of COVID-19 illness and poorer prognosis upon infection. Likewise, an increased frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 58 publications
1
55
0
2
Order By: Relevance
“…Insulin/IGF signaling plays a central role in the regulation of systemic energy homeostasis [14] , [15] . Emerging studies have shown that COVID-19, in some cases, predisposes patients to develop metabolic complications during or after the recovery process, such as insulin resistance, hyperglycemia, hyperlipidemia, and new onset of diabetes [13] . In the present study, we showed that SARS-CoV-2 infection caused impairment of the insulin/IGF signaling pathway in important metabolic tissues and endocrine cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin/IGF signaling plays a central role in the regulation of systemic energy homeostasis [14] , [15] . Emerging studies have shown that COVID-19, in some cases, predisposes patients to develop metabolic complications during or after the recovery process, such as insulin resistance, hyperglycemia, hyperlipidemia, and new onset of diabetes [13] . In the present study, we showed that SARS-CoV-2 infection caused impairment of the insulin/IGF signaling pathway in important metabolic tissues and endocrine cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5 % of infected people progress to serious stages with respiratory failure, septic shock, and acute respiratory distress syndrome (ARDS) [2] . The infection causes host cell and tissue damage and, in some cases, it triggers metabolic abnormalities, such as insulin resistance, hyperglycemia, abnormal lipid control, abnormal amino acid control, and new onset of diabetes [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . However, the molecular mechanisms have not yet been fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…Because patients diagnosed with COVID‐19 have been reported to develop diabetes more frequently and might be at increased risk for hyperglycemia, 9 vaccines that produce virus‐like proteins could similarly make recipients develop or exacerbate diabetes, and have recently been reported to worsen glycemic control. 5 , 6 , 7 , 8 Although most of the cases concluded to be the onset or exacerbation of type 2 diabetes occurred early after the first or second vaccination, 5 , 6 , 7 the diagnosis of type 1 diabetes took a relatively long period (4–8 weeks) after the second vaccination, including the previously reported 8 case as well as the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled DM remained the most common co-morbidity in both the groups of the current study. Some of the recent studies have implicated COVID-19 infection in the genesis or worsening of hyperglycemia [ 12 , 13 ]. In the non-COVID group, all patients were long-term diabetics, except one case of freshly detected DM.…”
Section: Discussionmentioning
confidence: 99%